Science, Religion, and Ethics: A Response to Michael J. Reiss - Soskice, Janet Martin (Zygon, 2019)
The respondent agrees with Michael Reiss's general diagnosis of the rudderless state of ethics in our modern society, but not with all of his account of its causes or possible solutions. Scripture has always been limited in terms of direct moral commands, and secular ethics has, since Aristotle at least, been influential in directing Christian understanding of the "good life." Ethics must be based in biology, but evolutionary biology can tell us more readily what is, than guide us into "what ought" to be. Christian teaching classically emphasized moral formation, grounded in the understanding that we are creatures of a good Creator. We have our being as gift, and human life flourishes when oriented to the Good.